2017
DOI: 10.1177/1759313117702919
|View full text |Cite
|
Sign up to set email alerts
|

Wave attenuation in presence of mangroves: A sensitivity study for varying bottom slopes

Abstract: Mangroves thrive in the intertidal areas (interface between land and sea) of tropical and subtropical belt and play an important role in overall attenuation of nearshore waves. Multiple interactions of waves with mangrove trunks and roots and bottom friction are the two primary mechanisms responsible for wave attenuation in mangrove forests. Earlier studies, comprising both analytical and experimental, reported an exponential decay in wave height for waves propagating over vegetation with idealized bottom topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Reference [36] studied the effectiveness of the Kanika Sands Mangrove Island near Dhamra in Odisha, India in attenuating cyclone-induced waves using the SWAN 40.81 model. Reference [37] conducted a sensitivity study with varying bottom slopes on wave attenuation in the presence of mangroves, and their results revealed that the wave height decays exponentially for mild slopes, found to be consistent with earlier studies; however, as the bottom steepness increases, the wave height reduction gradually increases. There are patches of mangrove forests along the coast of India, with varying vegetation density and diameter, but most of these areas are inaccessible for deploying sensors and conducting wave measurements.…”
Section: Introductionsupporting
confidence: 78%
“…Reference [36] studied the effectiveness of the Kanika Sands Mangrove Island near Dhamra in Odisha, India in attenuating cyclone-induced waves using the SWAN 40.81 model. Reference [37] conducted a sensitivity study with varying bottom slopes on wave attenuation in the presence of mangroves, and their results revealed that the wave height decays exponentially for mild slopes, found to be consistent with earlier studies; however, as the bottom steepness increases, the wave height reduction gradually increases. There are patches of mangrove forests along the coast of India, with varying vegetation density and diameter, but most of these areas are inaccessible for deploying sensors and conducting wave measurements.…”
Section: Introductionsupporting
confidence: 78%
“…According to Chen et al [54], the surge induced by wave was up to 0.55 m due to the giant typhoon generated waves and the steep sea-bottom slope in the northeastern coast of Taiwan. As reported by Parvathy and Bhaskaran [55], waves propagating on a steeper slope will have a severer energy dissipation over a narrower surf zone as compared to those on a gentler slope. Because of the gentle slope of NECS, the wave breaks early in the offshore and deforms gradually towards the shore [56].…”
Section: Contributions Of Wave-current Interaction To Water Level and Currentmentioning
confidence: 62%
“…Wave energy dissipation caused by wave deformation is merely a function of wave parameters (height, length, and period) and depths, especially in intertidal zone morphology and can be estimated numerically if these parameters are known [1,22]. According to Parvathy and Bhaskaran (2017), steep slopes' shoal distances become short, while the reduction in the height and part of surface waves may be reflected from the steep bottom [23]. On the other hand, mild slopes have a longer wave traveling distance and the waves will decay on mild slopes via the mangroves.…”
Section: Wave Dissipation By Mangrovesmentioning
confidence: 99%
“…Higher wave energy attenuated in coastal regions changes directly towards the bathymetric profile [23]. The bathymetric condition also influences the size of waves with an increase in depth along the distance from the coastal regions.…”
Section: Bathymetrymentioning
confidence: 99%
See 1 more Smart Citation